Dolichocolon Presenting with Bilateral Hydronephrosis in a Neonate. (20th March 2021) - Gielen, Laura; Raaijmakers, Anke; De Groote, Bert; ter Haar, Eva
Abstract : Background . Dolichocolon is an inborn anatomic variant of the colon with redundancies often causing constipation and/or volvulus presenting in childhood, adolescence, or adulthood. To the best of our knowledge, this is the first case of dolichocolon presenting in infancy with constipation and bilateral hydronephrosis. Case Presentation . A nineteen-day-old neonate presented to the emergency department with severe constipation and discomfort. During his admission, he developed pyelonephritis, and subsequent ultrasound of the kidneys and bladder showed bilateral hydroureteronephrosis. A barium enema was performed and it showed a dolichocolon. Enemas and lactulose were initiated with good effect on both the constipation as well as the hydronephrosis. Conclusions . Dolichocolon in a neonate can cause severe constipation which could also lead to an obstructive nephropathy if untreated. Monitoring of urine flow might be indicated when a neonate presents with severe constipation.